DINAMIKA KELOMPOK TANI PADI SAWAH DI DESA KARUA KECAMATAN BALUSU KABUPATEN TORAJA UTARA (Dynamics of Lowland Rice Farmers Group in Karua Village, Balusu Sub District, North Toraja Regency) - Angga Sari Pasoloran; Jenny Baroleh; Esry O. H. Laoh (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this study is to understand and describe the dynamics of lowland rice farmer groups in Karua Village, Balusu Sub District, which is studied from the aspects of farmer group dynamics. This research was conducted from August 2021 to September 2021. The data collected in this study were primary data obtained from direct interviews with farmer groups using a questionnaire. Secondary data were obtained from agencies related to this research, including the Department of Agriculture, Balusu Agricultural Extension Center, as well as data related to this research taken from the internet. Sampling by purposive sampling, namely from the population of rice farmers' groups totaling 177 people, the samples taken were 70 respondents.The research results showed that the dynamics of farmer groups in Karua Village, Balusu Sub District, assessed from the aspects of group dynamics consisting of group communication, conflict within groups, cohesion within groups, strength in groups, and problem solving in groups belonged to the near dynamic category.